If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1x = 7squared Combine like terms: 4x + -1x = 3x 3x = 7squared Solving 3x = 7adeqrsu Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 2.333333333adeqrsu Simplifying x = 2.333333333adeqrsu
| 2n-8+6n=-14+8n | | 2z-15+3z=5-5z+10 | | 4(b-12)+1=17 | | 2x+32=60 | | 11+3x=15+9x-3x | | 2(m+1)+2=10 | | X-5x=6-2x+5 | | -24x+18=4 | | 3v+6=0 | | -7+x=7+9-5 | | -16=5v+11 | | 9x+6=3(x-4) | | -6+7k=1+7k | | 0.2x-1.6=2.4x+2.7 | | -8w+4=0 | | 2(r+7)=-4 | | 4m-3n=8form | | 7x+263.5=2717 | | 5b+3(b-4)=2(y+3) | | 3x+6(-2)=24 | | 0.6x+1.9=5 | | 5b+3(b-4)=2(y+2) | | -25x+1+10=10z+1 | | 5b+3(3-4)=2(y+2) | | 1.8c+32=39.2 | | 1.5x+3.4=7.9 | | y=2x+75 | | 5b+3(b-4y)=2(y+2) | | -5u+2=12 | | 5b+3(3-4y)=2(y+2) | | 11=2h+3 | | 6x-15=4x+30 |